A multilevel gradient structural carbon derived from naturally preprocessed biomass. (30th October 2020) - Wang, Chao; Wang, Hanwei; Yang, Caixia; Dang, Baokang; Li, Caicai; Sun, Qingfeng
Abstract: Utilizing biomass as a precursor for preparing heteroatom-doped multilevel gradient carbon with few usage of chemical reagents and by a facile fabrication process is still a great challenge. Herein, a naturally preprocessed biomass product is elaborately chosen as the precursor, and it is directly converted into a multilevel gradient structural N, S co-doped carbon without complicated chemical pre-treatment process. As a result, using the naturally preprocessed biomass product as the precursor not only greatly reduces the usage of chemical activation agents but also endows the obtained porous carbon plentiful mesopores and a high specific surface area. Specifically, the carbon materials exhibit excellent electrochemical properties for supercapacitor. This work anticipates to provide new perspectives for the direct synthesis of high quality porous carbon materials with naturally pre-treated biomass as precursors. Graphical abstract: With ultralow usage amount of chemical activation reagent, a multilevel honeycomb structural N, S co-doped porous carbon from naturally preprocessed biomass product was successfully fabricated. Image 1 Highlights: A naturally preprocessed biomass is proposed as the precursor of porous carbon. A multilevel gradient structural N, S co-doped porous carbon is prepared. This work integrates high capacitive capability and low dosage of chemical reagent.